UJI VALIDASI METODE DAN PENETAPAN KADAR RANITIDIN DALAM SEDIAAN TABLET SECARA SPEKTROFOTOMETRI UV: METHOD VALIDATION TEST AND DETERMINATION OF RANITIDINE CONTENT IN TABLET PREPARATIONS BY UV SPECTROPHOTOMETRY - Dona, Rahma; Ningrum, Tilar Eka Widia; Nasution, Musyirna Rahmah; Fernando, Armon; Syahbandi, Ilham; Milianty, Jesy (JFL : Jurnal Farmasi Lampung, 2024)
This study aims to determine the levels of ranitidine in generic and trade name tablet preparations by UV spectrophotometry. Based on the results obtained linearity value of r = 0.9999 with limit of detection (LOD) 0.1667 ppm and limit of quantitation (LOQ) 0.5558 ppm. Precision obtained RSD results of 0.641% and in accuracy obtained % recovery at 3 concentrations of 9, 12 and 15 ppm respectively 101.05; 100.63; and 100.33%. The results of the determination of levels in ranitidine tablet preparations with five generic tablets and five trade name tablets have met the requirements for levels in medicinal preparations for ranitidine tablet preparations according to the Indonesian Pharmacopoeia VI Edition, which contains ranitidine not less than 90.0% and not more than 110.0%. It can be concluded that the UV spectrophotometric method used in the study has met the parameters set in the validation test so that this method can be applied to the analysis of determining ranitidine levels in a laboratory. Keywords:  Ranitidine, UV Spectrophotometry, Method validation